If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -1 = 103 Reorder the terms: -1 + 15y = 103 Solving -1 + 15y = 103 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 15y = 103 + 1 Combine like terms: -1 + 1 = 0 0 + 15y = 103 + 1 15y = 103 + 1 Combine like terms: 103 + 1 = 104 15y = 104 Divide each side by '15'. y = 6.933333333 Simplifying y = 6.933333333
| 9x-38=4x+23 | | 11-(x-2)=3 | | 4x+6=9x+1 | | 3x+3(5x-15)=63 | | 8+c=0 | | 8=c-12 | | x^2-14x+40=40 | | -0.23076923p=-2 | | -4(t-4)+9t=7t-6 | | (x-10)(x-4)=40 | | -3(1.2)(1.2)= | | 7y+5=9y | | 36.86=7g+3.54 | | -16-2n=n-4 | | 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 | | 2a+7=5a+1 | | -0.231p=-2 | | 26-9x=10+7x | | -5x+15=-2x+3 | | 3a+4=6a-2 | | 2x^2+mx+3=x+1 |